Training habits and medical characteristics of young swimmers in the Western Cape : an overview - Jaffer, Mohammed Nasir (MRC/UCT RU for Exercise and Sport Medicine, 2014)
Very little data exists on swimmers in South Africa. A series of three studies were undertaken to assess the medical status of young swimmers in the Western Cape, their training habits and how these related to performers. The aim of the first study was to determine the training habits of young competitive swimmers, whether there were gender differences in training, and whether the training habis changed over a three-year period (1995-1998). The second study assessed the prevalence of existing medical conditions in young competitive swimmers and whether there were gender differences amongst the swimmers for the various medical conditions. In the third study, mood changes in young competitive swimmers were monitored over a swimming season to determine whether a relationship exists between mood states and swimming performance.